2005
DOI: 10.1007/s11738-005-0053-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on physiological characteristics, yield and quality of microtubers in vitro in potato

Abstract: Ab stractIn vi tro microtuberization pro vides an ad e quate ex per i men tal model for the phys i o log i cal and met a bolic stud ies of tuberization and the pre lim i nary screen ings of po ten tial po tato geno types. The ef fects of sa line stress at 0-80 mmol con cen tration on in vi tro tuberization of two po tato cultivars were in vesti gated in this study. With an in crease in the salt con cen tra tion, the microtuberization of po tato was ei ther de layed by 5-10 days (20 and 40 mmol NaCl) or in hib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 28 publications
5
19
0
Order By: Relevance
“…These differences were expected due to the different genetic back ground, breeding origin, and maturity group of the examined genotypes. In harmony with our results, several reports demonstrated genotypic differences in salt tolerance in potato (Kharis et al, 1998;Zhang et al, 2005;Sudhersan et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These differences were expected due to the different genetic back ground, breeding origin, and maturity group of the examined genotypes. In harmony with our results, several reports demonstrated genotypic differences in salt tolerance in potato (Kharis et al, 1998;Zhang et al, 2005;Sudhersan et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…The observed decreases in microtuberization under salt stress are in agreement with the results of Zhang and Donnelly (1997) and Zhang et al (2005). Under the conditions of this study, significant differences among potato genotypes were found, in response to in vitro salt stress.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For example, salt stress has been shown to inhibit the growth of plant seedlings and roots in rice and wheat (Lin and Kao 1996;Xia et al 2000;Zhu et al 2002), as well as affecting the leaf chlorophyll and photosynthetic functions in sweet potato and wheat (Ke and Pan 1999;Zhu et al 2002). Salinity can also induce the accumulation of proline and malondialdehyde (MDA) in rice and potato (Lin and Kao 1996;Martinez et al 1996;Zhang et al 2005a) and change the activities of various antioxidant enzymes in several crops (Sairam and Srivastava 2002;Rios-Gonzalez et al 2002;Meloni et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Tuberization in potato was controlled by the tuberonic acid and its glucosides which had a close relation with JA in structure (Koda and Okazawa 1988, Yoshihara et al 1989). In addition, in vitro microtuberization provided an adequate experimental model for the physiological and metabolic studies of tuberization and the screening of potential potato genotypes (Li et al 2004, Zhang et al 2005a. The purpose of this work was to investigate the effects of different concentrations of JA on the growth and development of potato plantlets and microtubers under in vitro conditions.…”
mentioning
confidence: 99%